Voice, Sound and Noise: Theory and Practice of (Eco)aesthetical Education - Duoblienė, Lilija (Problemos, 2018)
[full article and abstract in Lithuanian; abstract in English]Together with images, sound also has tremendous impact on the perception of the world, and studies devoted to sound in education are still comparably scarce. For that reason, in this paper we attempt to understand why and how does the voice, sound, and especially noise become an object, instrument and an environment of education. The ideas proposed by critical pedagogy began to be applied in practice toward voice discourse analysis a few decades ago. Meanwhile the concepts and ideas of postmodern and posthumanist philosophy and their followers in the educational philosophy are neither simple nor easily applicable to sound and to noise as unpleasant sound. Nevertheless, new projects of sound in educational practice are being tested and implemented, in many cases still in connection with the approach of critical pedagogy to voice discourse. Despite different epistemological and ontological views on education in critical pedagogy and postmodernism, and although their link lacks justification and seems doubtful, the experiments presented in the article are innovative, rather successful and useful for the development of (eco)aesthetical education.
Keywords: sound; noise; voice; education; ecology; aesthetic